Analisis Pelaksanaan Akad Bai’ Bitsaman Ajil dan Penetapan Margin Keuntungan Pada Pembiayaan Modal Kerja Usaha Mikro Di Baitul Maal Wa Tamwil Muamalah Tulungagung - Arga Fajar Mustofa; Mei Santi; Hasan Sultoni (Journal of Islamic Banking, 2020)
Financing products with a bai' bitsaman ajil contract is one of the financing products offered by BMT Muamalah Tulungagung and is a type of product that is quite in demand by micro businesses to meet working capital needs such as for purchasing goods or business equipment and other productive working capital needs. However, in practice, there are still many people who tend to equalize the implementation and consider the profit margins determined to be similar to those in conventional banks. So it needs to be further investigated, with the formulation of the problem in this study, namely: How is the implementation of the bai’ bitsaman contract on the financing of working capital for micro businesses in BMT Muamalah Tulungagung? and What is the technique for determining the profit margins of the bai’ bitsaman ajil in financing working capital for micro businesses in BMT Muamalah Tulungagung?. This research belongs to the type of field research with a qualitative research approach and data collection is done by observation, interview and documentation techniques. Based on the results of the study, it can be stated that the implementation of the bai’ bitsaman ajil in financing contract on microbusiness working capital financing in BMT Muamalah Tulungagung is carried out through two models, namely the bai’ bitsaman ajil in financing contract in a pure manner and the bai’ bitsaman ajil in financing a covenant with the inclusion of wakalah contract. Basically, the implementation refers to sharia provisions, but in the implementation, especially the bai’ bitsaman ajil in financing contract by including wakalah agreement has not been fully implemented in accordance with the provisions of the DSN-MUI Fatwa. While the technique of determining profit margins for bai’ bitsaman ajil in financing working capital for micro businesses in BMT Muamalah Tulungagung has been carried out based on sharia provisions, which is carried out through an agreement between the BMT and members and in the determination of profit margins is carried out through considerations as determined at the meeting ALCO Islamic bank. Keywords: Bai’ Bitsaman Ajil, Margin, Financing, Working Capital.